2014
DOI: 10.1080/02705060.2014.971448
|View full text |Cite
|
Sign up to set email alerts
|

Behavior and growth of juvenile brown trout (Salmo trutta) following upstream and downstream displacement

Abstract: Juvenile brown trout were experimentally displaced 400 m both upstream and downstream, whereupon growth and homing behavior were examined for three months. No obvious signs of homing behavior were detected, no matter what the direction of displacement was, although an increased activity in displaced fish was detected. Our findings generally support the restricted movement paradigm, at least under favorable habitat conditions and low densities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…However, there are known successful spawning sites at both sites thus we know individuals are being produced in both areas and the distance between the sites are relatively long with multiple natural and man‐made obstacles making the displacement theory less likely. In support, juvenile anadromous brown trout have limited dispersal within a stream (Höjesjö et al., 2015 ; Palm et al., 2023 ; Vøllestad et al., 2012 ) and generally stay in the area in which they are born prior to migration (Quinn et al., 2012 ). Thus, where a juvenile is found could be considered approximate to the distance migrated upstream by its parents.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are known successful spawning sites at both sites thus we know individuals are being produced in both areas and the distance between the sites are relatively long with multiple natural and man‐made obstacles making the displacement theory less likely. In support, juvenile anadromous brown trout have limited dispersal within a stream (Höjesjö et al., 2015 ; Palm et al., 2023 ; Vøllestad et al., 2012 ) and generally stay in the area in which they are born prior to migration (Quinn et al., 2012 ). Thus, where a juvenile is found could be considered approximate to the distance migrated upstream by its parents.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it is hypothesized that translocated brown trout were more motivated to pass the impediment because they were performing a homing movement (Armstrong & Herbert, 1997; Harcup & Williams, 1984). In contrast, the majority of non‐translocated fish will not pass due to lack of motivation; instead they remained in their existing home range with non‐passage approaches to the impediment likely attributed to exploratory movements after release (Höjesjö et al, 2015) rather than an attempt to pass. With all key life‐stage habitats present downstream of the weir (e.g., refuge, feeding, and spawning habitat), over time the fish population may have increased in residency, similar to those in other studies (Branco et al, 2017; Bravo‐Córdoba et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This is probably because the potential to acquire food and grow varies little spatially in a system where productivity remains high year‐round. In such an environment, patch switching may be detrimental to fitness as it increases risk of predation (Höjesjö, Johnsson, & Bohlin, ). The maximum home range in this study (470 m) was similar to those reported elsewhere for brown trout, e.g.…”
Section: Discussionmentioning
confidence: 99%